Crowdfunding for sustainability ventures - Bento, Nuno (2022)
Sustainable entrepreneurship is raising and already providing a response to environmental, social and economic issues. However, it is still at disadvantage when seeks funding from traditional providers of capital. Crowdfunding has opened a new possibility for closing such funding gap. This study investigates the role of crowdfunding as a creative source of capital for ventures with sustainable orientation. The analysis seeks to understand to what extent project characteristics influence the ability to raise funds on the world leading reward-crowdfunding platform, and, importantly, to explain their survival post-campaign. Results show that the perceived sustainable mission positively influences the outcome of the campaign. An average survival rate over 70% after one year of operations suggests the creation of healthy sustainability ventures through crowdfunding. Furthermore, a higher percentage of female co-founders improves the chances of success during and after the crowdfunding campaign. The paper discusses implications for the success of crowdfunding campaigns and their development post-campaign in sustainable entrepreneurship.